2020
DOI: 10.3389/fnins.2020.00787
|View full text |Cite
|
Sign up to set email alerts
|

Combined Brain-Perfusion SPECT and EEG Measurements Suggest Distinct Strategies for Speech Comprehension in CI Users With Higher and Lower Performance

Abstract: Cochlear implantation constitutes a successful therapy of inner ear deafness, with the majority of patients showing good outcomes. There is, however, still some unexplained variability in outcomes with a number of cochlear-implant (CI) users, showing major limitations in speech comprehension. The current study used a multimodal diagnostic approach combining single-photon emission computed tomography (SPECT) and electroencephalography (EEG) to examine the mechanisms underlying speech processing in postlingually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 120 publications
0
24
1
4
Order By: Relevance
“…The impact of auditory deprivation and DoD on postoperative performance has to be taken into account while counseling suitable candidates for CI 6‐8 . Positron emission tomography results show a correlation between degree of cortical activation and speech therapy results 9,10 . Cochlear implantees who have used acoustic hearing aids before cochlear implantation tend to have better hearing results than those who have not used a hearing aid preoperatively 11‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of auditory deprivation and DoD on postoperative performance has to be taken into account while counseling suitable candidates for CI 6‐8 . Positron emission tomography results show a correlation between degree of cortical activation and speech therapy results 9,10 . Cochlear implantees who have used acoustic hearing aids before cochlear implantation tend to have better hearing results than those who have not used a hearing aid preoperatively 11‐14 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown the increased activation of frontal regions, specifically the inferior frontal gyrus, in speech perception, where larger activity is correlated with better performance (Eisner et al, 2010;Giraud et al, 2011;Kessler et al, 2020;Lee et al, 2007;Mortensen et al, 2006;Strelnikov et al, 2015;Suh et al, 2015). This change occurs before obtaining a CI and its level of activation before implantation is predictive of performance outcomes afterwards (Suh et al, 2015).…”
Section: Working Memory and Speech Perception Related To Clinical And...mentioning
confidence: 99%
“…Brain imaging studies corroborate this theory of increased use of the cognitive reserve in those with hearing loss, CI users and NH individuals presented with noise vocoded speech. Studies show a greater deployment of resources along with increased recruitment of temporal, parietal and frontal areas (Ala et al, 2020;Alain et al, 2018;Becker et al, 2013;Campbell & Sharma, 2013, 2014Cartocci et al, 2018;Coez et al, 2014;Davis & Johnsrude, 2003;Decruy et al, 2020;Dimitrijevic et al, 2017;Glick & Sharma, 2017Hervais-Adelman et al, 2012;Kessler et al, 2020;Y.-S. Lee et al, 2016;Marsella et al, 2017;McMahon et al, 2016;Miles et al, 2017;Obleser & Weisz, 2012;Paul et al, 2021;Petersen et al, 2015) and modified connectivity (Bidelman et al, 2019;Campbell & Sharma, 2020;Davis & Johnsrude, 2007;Husain & Schmidt, 2014; Y. S. Lee et al, 2018;Murphy et al, 2020;Palva et al, 2010;Pessoa et al, 2002;Petrides & Pandya, 2002;Prince et al, 2021;Puschmann & Thiel, 2017;Schmidt et al, 2013;Sohoglu et al, 2012;Wild et al, 2012;Wolak et al, 2019;Zekveld et al, 2012) during perception, encoding, and retention of visual, auditory and verbal stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different ways to process phonological tasks have been described and correlated to speech outcome in CI users by fMRI [Lazard and Giraud, 2017] and in SPECT and EEG studies [Kessler et al, 2020]. Whereas CI users with higher speech performance showed additional activations of parietal and occipital regions, those with lower performance used superior frontal areas during speech processing.…”
Section: Introductionmentioning
confidence: 99%